Bioactivity of Purple Yam Tuber (Dioscorea alata L.) on the Level of CD8+and CD8+CD462L+ T cells and Histology of Liver in BALB/c Mice Model of Digestive Allergy - Christina, Yuyun Ika; Rifa'i, Muhaimin (Graduate School, Universitas Brawijaya, 2014)
Purple yam tuber (Dioscorea alata L.) is a family of Dioscoreaceae containing diosgenin which is known as immunomodulatory agent. This study aimed to understand the quantitative changes of naïve and activated memory of T cells on mice model of digestive allergy after orally treated with ethanol extract of purple yam tuber. In this experiment, architecture of hepar histopathology is also observed. Ethanol extract of purple yam tuber with three doses of 0.167 g/kg bw (U1), 2.008 g/kg bw (U2), and 10.039 g/kg bw (U3) are applied. Data were analyzed using One-way ANOVA (p <0.05) and Tukey test using SPSS 16.0 for Windows. Ethanol extract of purple yam tuber triggers the immunocompetent activity of T cells in mice model of digestive allergy. The result showed that the number of memory type T cells in mice model of digestive allergy decreased in lower dose (0.167 g/kg bw (U1). However, the number of naïve T cells, CD8+CD62L+ in mice with digestive allergy after administration of purple yam tuber ethanol extract increased significantly in lower dose (0.167 g/kg bw (U1) compared with positive control (OVA). Dose variations of extract ethanol of purple yam tuber (0.167 g/kg bw) has a significantly effect to shift the T cell status from memory to naïve. Keywords: Digestive allergy, Dioscorea alata L., histopathology, immunomodulatory, subset T cells